Prevalence of common mental disorders among medical students in China: a systematic review and meta-analysis - Wang, Jinxingyi; Liu, Min; Bai, Jian; Chen, Yuhan; Xia, Jie; Liang, Baolin; Wei, Ruixuan; Lin, Jiayin; Wu, Jiajun; Xiong, Peng (Frontiers in Public Health, 2023)
Background The prevalence of mental distress is common for medical students in China due to factors such as the long duration of schooling, stressful doctor-patient relationship, numerous patient population, and limited medical resources. However, previous studies have failed to provide a comprehensive prevalence of these mental disorders in this population. This meta-analysis aimed to estimate the prevalence of common mental disorders (CMDs), including depression, anxiety, and suicidal behaviors, among medical students in China. Methods We conducted a systematic search for empirical studies on the prevalence of depression, anxiety, suicide attempt, suicide ideation, and suicide plan in Chinese medical students published from January 2000 to December 2020. All data were collected pre-COVID-19. The prevalence and heterogeneity estimations were computed by using a random-effects model and univariate meta-regression analyses. Results A total of 197 studies conducted in 23 provinces in China were included in the final meta-analysis. The prevalence data of depression, anxiety, suicide attempt, suicide ideation, and suicide plan were extracted from 129, 80, 21, 53, and 14 studies, respectively. The overall pooled crude prevalence for depression was 29% [38,309/132,343; 95% confidence interval (CI): 26%−32%]; anxiety, 18% (19,479/105,397; 95% CI: 15%−20%); suicide ideation, 13% (15,546/119,069; 95% CI: 11%−15%); suicide attempt, 3% (1,730/69,786; 95% CI: 1%−4%); and suicide plan, 4% (1,188/27,025; 95% CI: 3%−6%). Conclusion This meta-analysis demonstrated the high prevalence of CMDs among Chinese medical students. Further research is needed to identify targeted strategies to improve the mental health of this population.